IMPLEMENTASI METODE SERVQUAL UNTUK PENINGKATAN PELAYANAN PADA PABRIK ROTI CITRA - Syahfitri, Novianti; Nurwati, Nurwati; Santoso, Santoso (Smart Education, 2023)
Abstract: Citra Roti Factory is a business engaged in the manufacture and sale of bread. Sales data at the Citra Roti Factory fluctuated, namely sometimes sales increased and sometimes sales decreased. This is because the sales of bread at Citra bakery are also influenced by service. There are some customers who feel the quality of service is relatively low so that problem solving cannot be resolved optimally. The service period is relatively long so that the sales service process at the Citra bakery factory is slow, which is detrimental to customers. Human resources are still lacking so officers will find it difficult to provide services. To overcome these problems, a system was created to determine the quality of service provided to customers. The Service Quality method can be used as a measure of service quality. The results of this study are to determine the decision support system in the analysis of the service quality of selling bread that is applied at the Citra bakery factory. The application of the Service Quality method will speed up the decision-making process in analyzing the service level of bakery product sales at Citra bakery.Keywords: decision support system; service quality method; factory citra bread.Abstrak: Citra Roti Factory merupakan salah satu usaha yang bergerak di bidang pembuatan dan penjualan roti. Data penjualan di Pabrik Citra Roti berfluktuasi yaitu terkadang penjualan meningkat dan terkadang penjualan menurun. Hal ini dikarenakan penjualan roti di toko roti Citra juga dipengaruhi oleh pelayanan. Ada sebagian pelanggan yang merasa kualitas pelayanan relatif rendah sehingga dalam penyelesaian masalah tidak dapat diselesaikan secara optimal. Masa pelayanan yang relatif lama sehingga proses pelayanan penjualan di pabrik roti Citra lambat sehingga merugikan pelanggan. Sumber daya manusia masih kurang sehingga petugas akan kesulitan dalam memberikan pelayanan. Untuk mengatasi permasalahan tersebut maka dibuatlah suatu sistem untuk mengetahui kualitas pelayanan yang diberikan kepada pelanggan. Metode Service Quality dapat digunakan sebagai alat ukur kualitas layanan. Hasil dari penelitian ini adalah untuk mengetahui sistem pendukung keputusan dalam analisis kualitas pelayanan penjualan roti yang diterapkan di pabrik roti Citra. Penerapan metode Service Quality akan mempercepat proses pengambilan keputusan dalam menganalisis tingkat pelayanan penjualan produk bakery di Citra bakery.Kata Kunci: sistem pendukung keputusan; metode service quality; toko roti citra.